PREVALENCE AND FACTORS ASSOCIATED WITH MALNUTRITION AMONG CHILDREN AGED 6-59 MONTHS RECEIVING CARE AT TORORO GENERAL HOSPITAL, TORORO DISTRICT. A DESCRIPTIVE CROSS-SECTIONAL STUDY. - Oboth , Michael; Mutabazi, Tobius (Student's Journal of Health Research Africa, 2024)
Background Globally, 149.2 million children under the age of 5 years of age were stunted, 45.4 million Wasted, and 38.9 million overweight. In Uganda, an estimated 250,000 children are suffering from severe acute malnutrition which affects their gross well-being and life span. The purpose of the study was to establish the prevalence and factors associated with malnutrition of children aged 6-59 months receiving care at Tororo General Hospital, Tororo district. Methodology The study used a descriptive cross-sectional study design that used quantitative data collection methods. A stratified sampling method was used to select 30 respondents who responded to semi-structured questionnaires. Data was analyzed and presented using Microsoft Excel 2013 that presented it in the form of frequency tables, pie charts, and graphs. Results The prevalence of malnutrition was 30% and was associated with being female children, birth weights of less than 2500grams (55.6%), 2nd – 5th birth order (66.7%), mothers aged 18 – 24 years (44.5%), their mothers having no formal education (44.5%), weaning children before 6 months (88.9%), being more than 5 households residents (44.5%), having one meal per day (55.6%), mother not receiving husband’s support (66.7%), not having latrine at home (55.6%), poor solid waste management (66.7% ) and child having had severe sickness in the past one year (77.8%). Conclusion The prevalence of malnutrition among children was high at 30% and it was associated with a variety of factors such as low birth weight, young maternal age, childhood illness, low maternal education, poor breastfeeding practices, and poor hygiene. Recommendation Therefore, strategies should be put into practice to empower communities and mothers on how to improve the feeding behaviors of children as well as sanitation to aid in preventing these occurrences.